2018
DOI: 10.24818/amp/2018.30-07
|View full text |Cite
|
Sign up to set email alerts
|

Gender stereotypes at managerial positions in selected public institution

Abstract: The paper is focused on gender perception in a selected institution of public administration. The issue is considered a highly actual agenda deserving attention and research by means of which we can determine how perception of gender equality changes over time. The main goal of the article is to analyse managerial positions, find out and compare employees´ ideas of the chosen institution as to the compensation packages of men and women, find out the dependence of the institution´s success based on gender in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 2 publications
1
17
0
1
Order By: Relevance
“…Policies influence what work administrators do and who gets which jobs (Johnson and Crum-Cano, 2011). Gender stereotypes result in low representation of women in higher levels of management (Bohuslava, et al, 2018). As a result, organizations may fail to select women for leadership positions missing the talent and creativity of women (Voelck, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Policies influence what work administrators do and who gets which jobs (Johnson and Crum-Cano, 2011). Gender stereotypes result in low representation of women in higher levels of management (Bohuslava, et al, 2018). As a result, organizations may fail to select women for leadership positions missing the talent and creativity of women (Voelck, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In general, men still occupy the positions of power in the workplace and dominate decisionmaking (Acker, 2012;Connell, 2006;Eagly and Carly, 2007). Decision-making within the organization reinforces gender stereotypes resulting in low representation of women in higher levels of company management (Bohuslava et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many works, in particular, (Bausch, 2019), (Bilan et al, 2019a(Bilan et al, , 2018, (Brychko & Olejarz, 2019), (Munk et al, 2017), (Rudiawarni et al, 2020), (Vasilyeva et al, 2016(Vasilyeva et al, , 2019, (Shvindina, 2019) deal with the study of financial and business cycles based on time series analysis (seasonal, trend, cyclical component separation). Also there are a lot investigations about behavioral aspects in financial inclusion ( (Brychko, 2013), (Churilova et al, 2019), (Cortés-Sánchez & Rivera, 2019), (Djajanto et al, 2019), (Djalilov et al, 2015), (Hadbaa & Boutti, 2019), (Kaasa, 2019), (Katan et al, 2019), (Kolomiiets & Petrushenko, 2017), (Matošková, 2019), (Němcová & Staňková, 2019)) and protection of consumers ( (Piatek, 2018), (Poliakh, 2018), (Rehman, 2020), (Shapovalova et al, 2019), (Mihalčová et al, 2018)). Many scientific papers have found that the social safety of the population is also determined by the macroeconomic situation of the country (Aqil et al, 2019), (Bilan et al, 2019b, (Logan & Esmano, 2017), (Próchniak & Szyszko, 2019), (Packard et al, 2019); alternative factors related to the development of other sectors of the economy (industry, banking, investment, education) (Bilan et al, 2019c); (Buriak, 2015), (Ch & Semenog, 2017), (Klimontowicz, 2019), (Leonov et al, 2014(Leonov et al, , 2019, …”
Section: Literature Reviewmentioning
confidence: 99%